Pengaruh Karakteristik Individu terhadap Kemiskinan dan Peran Gereja dalam Pengentasan Kemiskinan (Studi Kasus di Kabupaten Cianjur, Jawa Barat) - Yulianus Viktor; Rilus A. Kinseng; Pudji Muljono (Sodality: Jurnal Sosiologi Pedesaan, 2023)
A significant challenge for developing nations, including Indonesia, is the occurrence of poverty. An example of a poverty-stricken area based on the number of poor people is Cianjur Regency. Therefore, this study aimed to analyze the influence of religiosity, work ethics, age, education, occupation, and gender on the poverty level. It also intended to examine the perspectives of churches in Cianjur regarding poverty and its role in poverty mitigation. The methodology used was a mixed method with 100 respondents, and the sample size was determined proportionally and randomly from churches located in Cianjur Regency. The results from the BPS (Central Bureau of Statistics) showed that 18% of the 100 respondents lived in poverty, as opposed to the remaining 82%. In terms of work ethics, 71%, 29%, and 0% belonged to the high, moderate, and low categories, respectively. The independent variables that significantly affect the poverty level are religiosity, age, and occupation. The independent variables that were not significant were work ethics, education, and sex. This study also shows that the five churches had diverse perspectives on poverty. Some actively implemented programs are aimed at poverty reduction, while others lack specific initiatives to address poverty.